2016
DOI: 10.1152/japplphysiol.00957.2015
|View full text |Cite
|
Sign up to set email alerts
|

High-phosphorus diet maximizes and low-dose calcitriol attenuates skeletal muscle changes in long-term uremic rats

Abstract: Although disorders of mineral metabolism and skeletal muscle are common in chronic kidney disease (CKD), their potential relationship remains unexplored. Elevations in plasma phosphate, parathyroid hormone, and fibroblastic growth factor 23 together with decreased calcitriol levels are common features of CKD. High-phosphate intake is a major contributor to progression of CKD. This study was primarily aimed to determine the influence of high-phosphate intake on muscle and to investigate whether calcitriol suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…However, phosphate excess is also toxic on skeletal muscle in the uremic rats. 6 These rats display slow-to-fast fiber-type transformation and increased muscle atrophy. 6 High Pi diet also induces ectopic skeletal muscle calcification in young mdx mice, a mouse model of muscular dystrophy with impairment in both cardiac and skeletal muscle function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phosphate excess is also toxic on skeletal muscle in the uremic rats. 6 These rats display slow-to-fast fiber-type transformation and increased muscle atrophy. 6 High Pi diet also induces ectopic skeletal muscle calcification in young mdx mice, a mouse model of muscular dystrophy with impairment in both cardiac and skeletal muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, up to 25% of US adults consume Pi at 3-4 fold higher than the recommended daily allowance on a regular basis. 5 Studies in uremic rats 6 and a mouse model of muscular dystrophy 7 have demonstrated skeletal muscle damage which was potentiated by dietary Pi excess. Recent studies from our group have also demonstrated that high Pi intake triggered augmented increases in sympathetic nervous system activity and blood pressure (BP) during muscle contraction in normal rats 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent literature, Acevedo et al . demonstrated that high-phosphorus diet potentiated adverse skeletal muscle changes in long-term uremic rats 11 . Inorganic phosphate had been observed to play an important role in muscle contractile function 12 , and increased inorganic phosphate was involved in skeletal muscle fatigue 13 .…”
Section: Introductionmentioning
confidence: 97%
“…Immunohistochemistry was performed with five monoclonal antibodies specific against MHC isoforms: BA–D5 (DMS, Braunschweig, Germany; anti–MHC–I), SC–71 (DMS; anti–MHC–IIa), BF–35 (DMS; anti–MHCs–I plus–IIa and–IIb), S5–8H2 (Biocytex Biotechnology, Marseille, France; anti–MHCs–I plus–IIx and–IIb), and BF–F3 (DMS; anti–MHC–IIb). The specificity of these monoclonal antibodies for MHCs in rat skeletal muscle has previously been reported [ 46 48 ]. The immunoperoxidase staining protocol with avidin–biotin complex (ABC) protocol was used as previously described [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The fibers in the selected area were classified according to their MHC content by means of visual examination of immunostainings of the five serial sections stained with the battery of anti–MHC monoclonal antibodies as previously described [ 46 , 47 ]. The reactivity of each individual muscle fiber in these five consecutive sections was judged as positive or negative by comparing the intensity of the reaction of neighbouring fibers.…”
Section: Methodsmentioning
confidence: 99%